2018
DOI: 10.1007/s00702-018-1899-8
|View full text |Cite
|
Sign up to set email alerts
|

Regional alterations of cerebral [18F]FDG metabolism in the chronic unpredictable mild stress- and the repeated corticosterone depression model in rats

Abstract: Preclinical research has been indispensable in the exploration of the neurological basis of major depressive disorder (MDD). The present study aimed to examine effects on regional brain activity of two frequently used depression models, the chronic unpredictable mild stress (CUMS)- and the chronic corticosterone (CORT) depression model. The CUMS and CORT depression model were induced by exposing male Long-Evans rats to a 4-week procedure of unpredictable mild stressors or a 3-week procedure of chronic corticos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Positron emission tomography with 18F-fluorodeoxyglucose ({18F} FDG) in Long-Evans rats chronically treated with corticosterone revealed decreased metabolic activity in the insular cortex and the striatum, but elevation in the cerebellum and midbrain [263]. Moreover, prolonged corticosteroids treatment led to structural changes in rodents' brains, such as reduced hippocampal volume and increased volume of amygdala (reviewed in [160]).…”
Section: Corticosterone Model Of Depressionmentioning
confidence: 99%
“…Positron emission tomography with 18F-fluorodeoxyglucose ({18F} FDG) in Long-Evans rats chronically treated with corticosterone revealed decreased metabolic activity in the insular cortex and the striatum, but elevation in the cerebellum and midbrain [263]. Moreover, prolonged corticosteroids treatment led to structural changes in rodents' brains, such as reduced hippocampal volume and increased volume of amygdala (reviewed in [160]).…”
Section: Corticosterone Model Of Depressionmentioning
confidence: 99%
“…In addition, decreased glucose uptake measured by PET in the striatum has been reported in a depression model in rats after chronic corticosterone administration [88]. Decreased CCO activity in brain regions included in the mesolimbic dopamine pathway play a key role in the motivational and/or hedonic processes is associated with anxiety and depression [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…Laeken and co-workers compared [ 18 F]FDG uptake (brain normalised uptake values) after CUMS exposure with tracer uptake after sub-chronic administration of corticosterone (as positive stress control). This study showed that the CUMS protocol displays only partially the brain inactivation/activation pattern that is induced by corticosterone administration [60]. Taken together, these studies indicate that the CUMS model has proven capable not only to induce depressive-like behaviour but also to modify the brain activity measured with [ 18 F]FDG-PET.…”
Section: Chronic-stress Paradigmsmentioning
confidence: 61%
“…No changes [40] Increased # , decreased^ [32] Decreased [21] Decreased [24] Cerebellum Increased [29,48] Increased [60] Decreased [24] *Postero-medial thalamic nuclei. ^These areas were reported as brainstem.…”
Section: Chronic-stress Paradigmsmentioning
confidence: 99%